2016
DOI: 10.14254/1800-5845.2016/12-1/4
|View full text |Cite
|
Sign up to set email alerts
|

Central and Eastern European Share Markets and the Halloween Effect

Abstract: The Halloween effect is one of the best known share market calendar anomalies. It is based on the phenomenon when the summer period (May -October) returns tend to be lower compared to the winter period (November -April) returns. This paper investigates the presence of the Halloween effect on share markets of 12 CEE countries. The results show that although the Halloween effect pattern can be found in the majority of the CEE share markets, it is statistically significant only in the case of Poland and Ukraine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This is consistent with Dichtl and Drobetz (2014) and Degenhardt and Auer (2018), who suggest that the Sell-in-May effect may have weakened after the publication of the seminal Bouman and Jacobsen (2002) study. Zhang and Jacobsen (2013) and Arendas and Chovancova (2016) also demonstrate that the strength of seasonal anomalies changes over time. If investors have come to expect higher November returns, some of them likely will buy more equities in October.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…This is consistent with Dichtl and Drobetz (2014) and Degenhardt and Auer (2018), who suggest that the Sell-in-May effect may have weakened after the publication of the seminal Bouman and Jacobsen (2002) study. Zhang and Jacobsen (2013) and Arendas and Chovancova (2016) also demonstrate that the strength of seasonal anomalies changes over time. If investors have come to expect higher November returns, some of them likely will buy more equities in October.…”
Section: Resultsmentioning
confidence: 91%
“…Zhang and Jacobsen (2013) and Arendas and Chovancova (2016) also demonstrate that the strength of seasonal anomalies changes over time. If investors have come to expect higher November returns, some of them likely will buy more equities in October.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Guo et al (2014) discovered a significant Halloween effect on the Chinese stock market over the 1997-2013 time period. Arendas and Chovancova (2016) concluded that the Halloween effect also impacts the stock markets in the Central and Eastern Europe (CEE) region. According to them, the Halloween effect can be found on stock markets of the majority of the 12 investigated CEE countries; however, it was statistically significant only in the case of Poland and Ukraine.…”
Section: Introductionmentioning
confidence: 99%